Pengaruh Human Relation dan Lingkungan Kerja Terhadap Kinerja Karyawan PT. Queen Ice Asia Bangkalan - Ika Inayatul Lutfiya; Lik Anah (Prodi Manajemen Fakultas Ekonomi Universitas Hasyim Asy'ari Tebuireng Jombang, 2022)
This research was conducted to find out partially and simultaneously the influence of human relations and work environment on performance at PT. Queen Ice Asia Bangkalan. This study uses quantitative methods, with data collection techniques through observation, interviews, and distributing questionnaires. The population is all employees of PT. Queen Ice Asia Bangkalan. The sample used was 35 people. The data analysis technique used is multiple linear regression. The results showed that: (1) Human relations partially positive and significant effect on the performance of employees of PT. Queen Ice Asia Bangkalan, (2) The work environment partially has a positive and insignificant effect on the performance of PT. Queen Ice Asia Bangkalan, (3) Human relations and work environment simultaneously affect the performance of employees of PT. Asian Ice Queen Bangkalan. Keyword: Human Relatio; Work environment; Employee Performance